Analisis Kinerja Electrostatic Precipitator (ESP) Berdasarkan Pembagian Besarnya Arus Transformator Di PT PJB UBJOM PLTU Paiton - jon, winarno (Faculty of Engineering, Universitas Brawijaya, 2020)
Electrostatic Precipitator (ESP) is a device that has the function of capturing the ashes of combustion contained in the exhaust gases before being discharged into the atmosphere through a stack / chimney, so that the discharged gases to be discharged do not contain ash particles that can pollute the environment. PT PJB UBJOM PLTU Paiton has 16 ESP transformers operating 24 hours. During the operating period there are disturbances and damage that causes ESP efficiency is reduced so there is a need to reset the transformer secondary current. It is intended that the efficiency of ESP is maintained and the exhaust gas does not pollute the environment. By using the